Penerapan Metode Pembelajaran Berprespektif Gender dalam Islam Untuk Guru PAUD - Desi Arpa; Tuti Nuriyati (JOEAI:Journal of Education and Instruction, 2022)
The purpose of this study is to describe gender in Islam and to describe the application of gender perspective learning methods in Islam for PAUD teachers. This research is a descriptive qualitative research and the data obtained is processed through data triangulation and then described in depth. The subjects in this study were teachers at Aisiyiyah Bengkalis Kindergarten which consisted of 10 educators, and for instruments the researchers used observation, interviews or distributing questionnaires. Data analysis in this study was carried out through three activities that occurred simultaneously, namely data reduction, data presentation, and drawing conclusions. The results of this study are Gender in Islam is equality in faith and piety, the measure of a person's glory in the sight of Allah is achievement and quality, regardless of ethnicity. In conclusion, the application of the Islamic perspective learning method in Aisiyah Kindergarten has not been implemented properly, only inserted in the themes in the curriculum, another thing that causes the implementation of this gender-based method is not due to the understanding and experience of teachers in the method of applying gender. Keywords: Gender, PAUD Teachers, Learning Methods.